2006
DOI: 10.1111/j.1365-2052.2006.01468.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bovine RNA polymerase III promoters for short hairpin RNA expression

Abstract: RNA interference (RNAi) mediated by DNA-based expression of short hairpin RNA (shRNA) is a powerful method of sequence-specific gene knockdown. A number of vectors for expression of shRNA have been developed that feature promoters from RNA polymerase III (pol III)-transcribed genes of mouse or human origin. To advance the use of RNAi as a tool for functional genomic research and for future development of specific therapeutics in the bovine species, we have developed shRNA expression vectors that feature novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…These nine loci are dispersed throughout the genome and fi ve were found to have associated promoter regions, each with different transcriptional activities. These fi ndings spurred the characterization and comparison of U6 promoters for shRNA transcription from a variety of other species including bovine ( 69,70 ) , chicken ( 71,72 ) , fugu ( 73 ) , zebra fi sh ( 74 ) , sheep ( 75 ) , and pig ( 76 ) .…”
Section: Promoters For Shrna Transcriptionmentioning
confidence: 98%
“…These nine loci are dispersed throughout the genome and fi ve were found to have associated promoter regions, each with different transcriptional activities. These fi ndings spurred the characterization and comparison of U6 promoters for shRNA transcription from a variety of other species including bovine ( 69,70 ) , chicken ( 71,72 ) , fugu ( 73 ) , zebra fi sh ( 74 ) , sheep ( 75 ) , and pig ( 76 ) .…”
Section: Promoters For Shrna Transcriptionmentioning
confidence: 98%
“…sequence element (PSE), a TATA like element and an enhancer region consisting of an octamer motif (OCT) and a SPH element (7)(8)(9). Recently, various U6 promoters for shRNA expression were reported in several species including chicken (10, 11), bovine (12,13), and pig (14). Here, we have cloned two sheep U6 promoters and analyzed their potential use as shRNA expression vectors.…”
Section: Cloning and Functional Analysis Of Sheep U6 Promotersmentioning
confidence: 98%
“…However, the human H1 promoter is usable in both human and mouse cells, while the mouse U6 promoter is restricted to mouse cells [80]. Lambeth et al [81] identified a bovine U6 promoter that was more potent than its mouse variant. To a lesser extent, the human 7SK promoter is gaining a lot of popularity due to its stronger nature compared to U6 [82].…”
Section: Rna Polymerase III Type 3 Promotersmentioning
confidence: 98%